Simulated Evaluation of Tooth Fracture Resistance during Instrumentation with Single-and Multi-file Rotary Systems - Godiny, Mostafa; Jalali, Seyed Kamal; Khavid, Atefeh; Fatahy, Ali (Iranian Endodontic Journal, 2021)
Introduction: Use of rotary files in root canal preparation is inevitable due to their high speed and reduced duration of treatment. However, microcracks and even root fracture may sometimes occur in teeth where canal(s) is/are prepared using these devices. The purpose of the current study was to compare NeoNiti single-file with RaCe multi-file rotary systems. Materials and Methods: An accurate scanner designed detailed three-dimensional file models, and a simulated model was developed using canal-specific features; including dentin thickness, root canal length, taper rate and root canal curvature. Cleaning and shaping conditions were simulated with appropriate speed and crack conditions for both types of files on the computer. Strain accumulation sites in the root dentin wall where microcracks was likely to occur were simulated and investigated. Abaqus and ANSYS software were used to perform finite element simulations. Results: RaCe files with 0.04 taper caused the lowest level of stress (34.33 MPa) to the simulated canal. Conversely, the highest level of stress (62.35 MPa) was applied by 8% NeoNiti file to the simulated canal. Conclusions: Based on the present experimental study, it can be concluded that RaCe multi-file rotary system may better be used in endodontic therapy, and the risk of microcracks in the tooth wall is less than that of NeoNiti single-file rotary system.